2022
DOI: 10.1093/infdis/jiac430
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies Identify an Association of Transferrin Binding Protein B Variation and Invasive Serogroup Y Meningococcal Disease in Older Adults

Abstract: Background Neisseria meningitidis serogroup Y, especially ST-23 clonal complex (Y:cc23), represents a larger proportion of invasive meningococcal disease (IMD) in older adults compared to younger individuals. This study explored the meningococcal genetic variation underlying this association. Methods Maximum-likelihood phylogenies and the pangenome were analysed using whole genome sequence (WGS) data from 200 Y:cc23 isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
2
0
0
Order By: Relevance
“…Few GWAS studies have been performed on N. meningitidis , and few similarities were found to this study [ 23, 67, 75 ]. These studies have found carriage-derived k-mers in the tspB gene [ 67 ], associations of tbpB with invasive serogroup Y, cc23 isolates [ 75 ] , and another study found the gene NEIS0975 associated with invasive isolates [ 23 ], which we here found to be associated with carriage. These studies focused on one serogroup or CC, which may explain why we found different variants as we studied the entire N. meningitidis population from 2018 to 2019 in Sweden.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Few GWAS studies have been performed on N. meningitidis , and few similarities were found to this study [ 23, 67, 75 ]. These studies have found carriage-derived k-mers in the tspB gene [ 67 ], associations of tbpB with invasive serogroup Y, cc23 isolates [ 75 ] , and another study found the gene NEIS0975 associated with invasive isolates [ 23 ], which we here found to be associated with carriage. These studies focused on one serogroup or CC, which may explain why we found different variants as we studied the entire N. meningitidis population from 2018 to 2019 in Sweden.…”
Section: Discussionsupporting
confidence: 69%
“…Despite adjustment for population structure as part of the GWAS approach, some results in this study may have been affected by the lower frequency of genetic variants among the major serogroups of the invasive isolates in Sweden. Few GWAS studies have been performed on N. meningitidis, and few similarities were found to this study [23,67,75]. These studies have found carriage-derived k-mers in the tspB gene [67], associations of tbpB with invasive serogroup Y, cc23 isolates [75], and another study found the gene NEIS0975 associated with invasive isolates [23], which we here found to be associated with carriage.…”
Section: Discussionsupporting
confidence: 53%